2023
DOI: 10.1101/2023.03.19.533383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutant Prion Protein Endoggresomes are Hubs for Local Axonal Organelle-Cytoskeletal Remodeling

Abstract: Dystrophic axons comprising misfolded mutant prion protein (PrP) aggregates are a characteristic pathological feature in the prionopathies. These aggregates form inside endolysosomes -called endoggresomes-, within swellings that line up the length of axons of degenerating neurons. The pathways impaired by endoggresomes that result in failed axonal and consequently neuronal health, remain undefined. Here, we dissect the local subcellular impairments that occur within individual mutant PrP endoggresome swelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…159,160 These aggregates are often located within dystrophic axonal domains, where accumulation of organelles (mitochondria), neurofilaments, and endosomal vesicles including enlarged lysosome-like structures that contain incompletely digested material, also occurs. 161165 A mutant prion protein (PrP) fusion construct containing an expanded 14 octapeptide repeat (PrP PG14 ; there is a 9 octapeptide insertion in wild-type PrP (PrP WT ); see Figure S5A) is associated with Gerstmann-Sträussler-Scheinker (GSS), a human familial prion disorder. 166 Previous work showed that expression of PrP PG14 in cultured murine hippocampal neurons results in the formation of enlarged endolysosomes along axons containing PrP PG14 aggregates, known as endoggresomes (aggregates within endosomes) (Figure S5A, bottom panels).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…159,160 These aggregates are often located within dystrophic axonal domains, where accumulation of organelles (mitochondria), neurofilaments, and endosomal vesicles including enlarged lysosome-like structures that contain incompletely digested material, also occurs. 161165 A mutant prion protein (PrP) fusion construct containing an expanded 14 octapeptide repeat (PrP PG14 ; there is a 9 octapeptide insertion in wild-type PrP (PrP WT ); see Figure S5A) is associated with Gerstmann-Sträussler-Scheinker (GSS), a human familial prion disorder. 166 Previous work showed that expression of PrP PG14 in cultured murine hippocampal neurons results in the formation of enlarged endolysosomes along axons containing PrP PG14 aggregates, known as endoggresomes (aggregates within endosomes) (Figure S5A, bottom panels).…”
Section: Resultsmentioning
confidence: 99%
“…166 Previous work showed that expression of PrP PG14 in cultured murine hippocampal neurons results in the formation of enlarged endolysosomes along axons containing PrP PG14 aggregates, known as endoggresomes (aggregates within endosomes) (Figure S5A, bottom panels). 165,167 Mutant and WT PrP sequences contain a PrP signal sequence (SS) and PrP glycosylphosphatidylinositol (GPI)-anchoring sequence to ensure proper transport through the secretory pathway within the lumen of vesicles and compartments. 167 Endoggresomes form within axonal dystrophic swellings following the active transport of PrP PG14 -carrying Golgi-derived vesicles into the axon by their association with the small endolysosomal GTPase ARL8b, which recruits kinesin-1 and the multiunit homotypic fusion and protein sorting (HOPS) complex subunit VPS41 onto PrP PG14 -carrying endosomes.…”
Section: Resultsmentioning
confidence: 99%